Characteristics and changes in characteristics of women and babies admitted to residential parenting services in New South Wales, Australia in the first year following birth: a population-based data linkage study 2000–2012 - Hannah G Dahlen; Charlene Thornton; Cathrine Fowler; Robert Mills; Grainne O'Loughlin; Jenny Smit; Virginia Schmied (BMJ Open)
Objective To examine the characteristics of women and babies admitted to the residential parenting services (RPS) of Tresillian and Karitane in the first year following birth.Design A linked population data cohort study was undertaken for the years 2000–2012.Setting New South Wales (NSW), Australia.Participants All women giving birth and babies born in NSW were compared with those admitted to RPS.Results During the time period there were a total of 1 097 762 births (2000–2012) in NSW and 32 991 admissions to RPS. Women in cohort 1: (those admitted to RPS) were older at the time of birth, more likely to be admitted as a private patient at the time of birth, be born in Australia and be having their first baby compared with women in cohort 2 (those not admitted to an RPS). Women admitted to RPS experienced more birth intervention (induction, instrumental birth, caesarean section), had more multiple births and were more likely to have a male infant. Their babies were also more likely to be resuscitated and have experienced birth trauma to the scalp. Between 2000 and 2012 the average age of women in the RPS increased by nearly 2 years; their infants were older on admission and women were less likely to smoke. Over the time period there was a drop in the numbers of women admitted to RPS having a normal vaginal birth and an increase in women having an instrumental birth.Conclusion Women who access RPS in the first year after birth are more socially advantaged and have higher birth intervention than those who do not, due in part to higher numbers birthing in the private sector where intervention rates are high. The rise in women admitted to RPS (2000–2012) who have had instrumental births is intriguing as overall rates did not increase.